2016
DOI: 10.1111/famp.12208
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of Literature on Expressed Emotion and Relapse in Patients with Schizophrenia Verified by a p‐Curve Analysis

Abstract: There is growing concern that much published research may have questionable validity due to phenomena such as publication bias and p-hacking. Within the psychiatric literature, the construct of expressed emotion (EE) is widely assumed to be a reliable predictor of relapse across a range of mental illnesses. EE is an index of the family climate, measuring how critical, hostile, and overinvolved a family member is toward a mentally ill patient. No study to date has examined the evidential value of this body of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 47 publications
1
36
0
1
Order By: Relevance
“…Another study carried out in Europe demonstrated that in the United Kingdom patients that live in homes with high levels of EOI have higher relapse rates in a 9-month period (1) . However, samples analyzed in other European countries do not show a relationship between EOI and relapses in schizophrenia (8,24) . An analysis carried out with a population of Mexican-Americans demonstrated that EOI may increase the risk of relapse in a 12-month follow-up period, but in longer periods the domain was not considered a predictor of relapse (25) .…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Another study carried out in Europe demonstrated that in the United Kingdom patients that live in homes with high levels of EOI have higher relapse rates in a 9-month period (1) . However, samples analyzed in other European countries do not show a relationship between EOI and relapses in schizophrenia (8,24) . An analysis carried out with a population of Mexican-Americans demonstrated that EOI may increase the risk of relapse in a 12-month follow-up period, but in longer periods the domain was not considered a predictor of relapse (25) .…”
Section: Discussionmentioning
confidence: 76%
“…Understanding of these aspects is essential to evaluate how different contexts influence levels of expressed emotion and prognosis of the disease (23) . According to a study carried out in China, developing countries present lower levels of expressed emotion (8) . Another study carried out in Europe demonstrated that in the United Kingdom patients that live in homes with high levels of EOI have higher relapse rates in a 9-month period (1) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations